2016
DOI: 10.1371/journal.pone.0166221
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Assisted Radical Cystectomy with Extracorporeal Urinary Diversion Does Not Show a Benefit over Open Radical Cystectomy: A Systematic Review and Meta-Analysis of Randomised Controlled Trials

Abstract: BackgroundThe number of robotic assisted radical cystectomy (RARC) procedures is increasing despite the lack of Level I evidence showing any advantages over open radical cystectomy (ORC). However, several systematic reviews with meta-analyses including non-randomised studies, suggest an overall benefit for RARC compared to ORC. We performed a systematic review with meta-analysis of randomised controlled trials (RCTs) to evaluate the perioperative morbidity and efficacy of RARC compared to ORC in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 36 publications
5
40
0
Order By: Relevance
“…In line with contemporary reports , RAZOR reported that RARC had significantly reduced blood loss and transfusion rates, but longer operating times. RAZOR did not provide a cost analysis for RARC vs ORC due to varying costs of RC across centres, but they reported a small albeit significant difference in length of stay between RARC and ORC (6 and 7 days, P = 0.022).…”
supporting
confidence: 78%
See 1 more Smart Citation
“…In line with contemporary reports , RAZOR reported that RARC had significantly reduced blood loss and transfusion rates, but longer operating times. RAZOR did not provide a cost analysis for RARC vs ORC due to varying costs of RC across centres, but they reported a small albeit significant difference in length of stay between RARC and ORC (6 and 7 days, P = 0.022).…”
supporting
confidence: 78%
“…ORC is less expensive, whereas RARC offers reduced blood loss and a potentially quicker recovery. Small randomised studies have shown similar complication rates and perioperative morbidity , and questioned the oncological efficacy of RARC. The health economics of robotic surgery is another key concern, as benefits from RARC are needed to offset the significantly higher operating costs.…”
mentioning
confidence: 99%
“…Recently published RCT between RARC and ORC showed a similar PSM rates (3.6% vs 4.8%, P = 0.7), and (6% vs 5%, P = 0.59) for RARC versus ORC, respectively . Also a met‐analysis have shown no difference between RARC and ORC in regards to margin rates …”
Section: Techniquementioning
confidence: 82%
“…The four RCTs have published their early outcomes, and the recent meta‐analysis by Tan et al . of those RCTs concluded that RARC is better for blood loss and wound complications, and worse for operation time . No other difference in terms of postoperative morbidity, PSM, lymph node yield, and LOS was found between RARC and ORC.…”
Section: Perioperative Outcomesmentioning
confidence: 94%
“…Since 2013, we have found 14 such analyses . Two of them are actually meta‐analyses of the four published RCTs . Table summarizes their results in a better or worse fashion, which represents a statistically significant difference between RARC and ORC.…”
Section: Perioperative Outcomesmentioning
confidence: 99%